The Effect of the Federal Trade Commission Improvements Act of 1980 on the FTC's Rulemaking and Enforcement Authority - Earl W. Kintner; Christopher Smith; David B. Goldston (Washington University Law Quarterly, 1980)
A more detailed analysis of the Federal Trade Commission Improvements Act of 1980 follows.
Keywords: United States. Federal Trade Commission; Federal Trade Commission Improvements Act of 1980; United States